A New Reagent to Detect Alkali Nitrites and Conversely Copper Ions - Mir, S.A.; Shakoor, A. (Asian Journal of Chemistry, 2010)
Alkali nitrites react specifically with cupric ions to form cupric nitrite imparting green colouration to the solution with intensity proportional to the concentration of the reactants. The colour is quantitatively decolorized by addition of dilute mineral acid. The reaction can be employed in routine qualitative analysis of nitrites and cupric ions and to differentiate nitrites from nitrates.